THE MEDIATING ROLE OF TOURIST LOYALTY ON PERSONAL MOTIVES, DESTINATION IMAGE, SATISFACTION AND REVISIT INTENTION TO ECOTOURISM DESTINATIONS OF MALAYSIA - Md Moinuddin Morshed; Raemah Abdullah Hashim; Rosli Mahmood; Nur Shazwani Rosli (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
The purpose of this study is to investigates the mediating effects of loyalty on the relationships between personal motives, destination image, satisfaction and revisit intention to ecotourism destinations of Malaysia. In terms of research methodologies, this study adopted cross-sectional study and quantitative research approach. The data for this study, the survey questionnaires were distributed by using intercept survey method and 400 respondents’ samples were collected from the three different national parks and ecotourism sites in Malaysia. By using quantitative research design, there are three hypotheses developed and tested by using Partial Least Squares (PLS-SEM: version 4) and SPSS (version 29) for demographic and descriptive analysis. The empirical findings of this study presented that loyalty mediated the relationship between, tourist’s satisfaction, destination image, personal motivates and revisit intention to the ecotourism destination of Malaysia. Based on the comprehensive literature and findings, this study attempted to make both academic and industry perspective contribution which engage with ecotourism one of the potential sectors of tourism industry in Malaysia. In theoretical contribution, this study addressed loyalty as mediating factor which has impact of the factors of tourist revisit intention. Mentioning the practical implication, the significant effect of tourist loyalty on the relationships between tourist’s satisfaction, destination image, personal motives and tourist revisit intention expressed the importance of tourist behavioural factors for increasing the revisit intention rate to the national parks. Finally, the study concluded the discussion on findings and implications.